When public health emergencies hit the front line: a qualitative study of the patient experience in the emergency department and outpatient infectious disease clinic during the 2022 Mpox clade IIb outbreak - Molly Brick; David Rudolph; Gaby Dashler; Amanda Varnauskas; Luxi Qiao; Matthew M. Hamill; Joyce L. Jones; William Garneau; Mustapha Saheed; Gabor Kelen; Kelly Gebo; Bhakti Hansoti (BMC Infectious Diseases)
Abstract Background The World Health Organization (WHO) declared mpox clade IIb a Public Health Emergency of International Concern (PHEIC) in July 2022. During the clade IIb epidemic, patients presented to both Emergency Departments (ED) and Infectious Disease (ID) clinics for care. Given the uncertainty and limited knowledge of mpox in 2022, we sought to understand the patient experience to inform service delivery for future outbreaks. Methods A retrospective qualitative study enrolled patients who presented to five EDs and one ID clinic in the Johns Hopkins Health System who tested positive for mpox virus (MPXV) between June 1 and December 31, 2022. Patient interviews were conducted in pairs with one researcher as the interviewer and a second as note-taker. A semi-structured interview guide with post-interview coding for content analysis was used to ascertain clinical factors, individual factors, and system factors that impacted the patient experience. Results Of 73 patients who tested positive for MPXV, 47 (64.4%) presented to EDs and 26 (35.6%) to the ID clinic; 23 (31.5%) agreed to participate [n = 13 ED, 27.7%; n = 10 ID, 38.5%]. All identified as male, median age was 36 years [IQR 31–41], 65.2% Black [n = 7 ED, 53.8%; n = 7 ID, 70.0%], 87.0% men who have sex with men [n = 10 ED, 76.9%; n = 10 ID, 100%], 69.6% were people living with HIV [n = 7 ED, 53.8%; n = 9 ID, 90.0%]. Participants diagnosed in EDs perceived difficulties with follow up and isolation, desired more information about tecoviromat, and nearly half reported no contact from local health departments for follow up care or tecoviromat access. Participants presenting to the ID clinic endorsed positive experiences tied to an established and trusted medical home. Stigma, loneliness, and mental health difficulties were consistent themes for all participants. Conclusion Patients present to various venues for infectious diseases such as mpox. Many present to EDs as a safety net service or for more severe disease manifestations. Institutional partnerships between ED, ID, and public health authorities, ongoing training, an on-call system for infectious disease threats, de-stigmatization, and focus on successful linkage-to-care pathways are potential ways to improve responses for future novel infectious disease outbreaks.